PERAN PEMERINTAHAN DESA DALAM PEMBERDAYAAN MASYARAKAT DENGAN PERUBAHAN SOSIAL TERHADAP KESEHATAN DI DESA CIBENING KABUPATEN BOGOR - Wahdiyana , Fika; Hamid, Muhammad; Aliza, Ozama Putra; Saspira, Ratih; STS, Ahmad (Fakultas Ilmu Dakwah dan Komunikasi, 2024)
Social change is the process of changing the structure or order of society, including more innovative ways of thinking and attitudes towards social life for a more dignified life. Figures who voiced social change include: Kingsley Davis, Mac Iver, Selo Soemarjan, William Ogburn. The tendency towards social change is a symptom that arises from the interaction of human life in society. Data collection techniques using observation, interviews and documentation. Based on the results of the research that has been carried out, it can be concluded that the Cibening village government has been able to empower the community through several empowerment programs, namely: first institutional activation, second increasing community participation by implementing community service activities, village musrenbang and physical development, third increasing the productive economy by activities to provide fish feed and seeds to farming communities. However, in implementing community empowerment efforts, the Cibening village government experienced obstacles including lack of community participation, a lazy culture and a lack of facilities available to support empowerment activities.